2015
DOI: 10.4331/wjbc.v6.i2.28
|View full text |Cite
|
Sign up to set email alerts
|

Animal venom studies: Current benefits and future developments

Abstract: Poisonous organisms are represented in many taxa, including kingdom Animalia. During evolution, animals have developed special organs for production and injection of venoms. Animal venoms are complex mixtures, compositions of which depend on species producing venom. The most known and studied poisonous terrestrial animals are snakes, scorpions and spiders. Among marine animals, these are jellyfishes, anemones and cone snails. The toxic substances in the venom of these animals are mainly of protein and peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 19 publications
1
87
0
4
Order By: Relevance
“…However, venom-based medical treatments have only recently received attention [39]. The current study indicated that pOh2, isolated from the venom of Vietnamese O. hannah snake, may be a potential candidate for obesity treatment.…”
Section: Discussionmentioning
confidence: 78%
“…However, venom-based medical treatments have only recently received attention [39]. The current study indicated that pOh2, isolated from the venom of Vietnamese O. hannah snake, may be a potential candidate for obesity treatment.…”
Section: Discussionmentioning
confidence: 78%
“…Poisonous, venom producing organisms, being a cause of mortality, have been a source of medicine to human syndrome since time immemorial. History says, in ancient Rome animal venoms were often used to diagnose smallpox, fever, leprosy and wound healing (Utkin 2015). One of the best contributions of animal venom in medical science is the discovery of bradykinin by Rocha e Silva and his team (Rocha e Silva et al 1949) to reduce contraction of isolated guinea pig ileum upon incubating globulin fraction of dog plasma with snake venom (obtained from Bothrops jararaca).…”
Section: Introductionmentioning
confidence: 99%
“…Venom-toxins exert their effect by interacting with a range of targets which include cellular receptors, membranes, and ion channels. α-Bungarotoxin (venom component of elapid snake Bungarus multicinctus), a type of α-neurotoxin proves to be fatal when it binds irreversibly to nicotinic acetylcholine receptor, is one of the best examples of the application of toxin in medical research (Utkin 2015;Young et al 2003). 'Tumour Paint' outlined by natural toxins or peptides from natural organisms (viz.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of species belong to the poisonous animal kingdom, such as chordates (reptiles, fishes, amphibians, mammals), echinoderms (starfishes, sea urchins), mollusks (cone snails, octopi), annelids (leeches), nemertines, arthropods (arachnids, insects, myriapods), and cnidarians (sea anemones, jellyfish, corals) [1]. Animal venoms are a rich source of natural compounds that have evolved to have high affinity and selectivity for a diverse range of biological targets.…”
Section: Introductionmentioning
confidence: 99%